1996
DOI: 10.1053/jhep.1996.v24.pm0008855178
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of prehepatic and hepatic metabolism of verapamil by rifampin

Abstract: Cytochrome P450 (CYP) enzymes, which metabolize numerous drugs, are expressed both in liver and in extrahepatic tissues. CYP3A4 for example is present and inducible by rifampin in epithelial cells of the gastrointestinal tract. It has been shown that such prehepatic metabolism contributes substantially to total clearance of CYP3A4 substrates (e.g., cyclosporine) before and even more pronounced during enzyme induction. We examined the effect of enzyme induction on prehepatic and hepatic metabolism of the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
100
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 3 publications
(7 reference statements)
10
100
0
1
Order By: Relevance
“…A similar study was reported in humans given intravenous and oral doses of verapamil, and the half-life of decrease in CYP3A activity after RIF withdrawal was estimated to be 1.5 to 2.1 days (Fromm et al, 1996). In another clinical study, urinary ratios of 6␤-hydroxycortisol to cortisol, an endogenous marker for CYP3A activity, returned to preinduction levels 11 days after RIF treatment was stopped (Tran et al, 1999), and the mean half-life of the return from maximum to basal levels was estimated to be 3 days (Yang et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar study was reported in humans given intravenous and oral doses of verapamil, and the half-life of decrease in CYP3A activity after RIF withdrawal was estimated to be 1.5 to 2.1 days (Fromm et al, 1996). In another clinical study, urinary ratios of 6␤-hydroxycortisol to cortisol, an endogenous marker for CYP3A activity, returned to preinduction levels 11 days after RIF treatment was stopped (Tran et al, 1999), and the mean half-life of the return from maximum to basal levels was estimated to be 3 days (Yang et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…Monkeys also show poor oral bioavailability for other CYP3A substrates such as verapamil (ϳ1%), nifedipine (ϳ1%), methotrexate (8%), and simvastatin (0.8%), which are therefore not well suited for in vivo enzyme induction study (Ogasawara et al, 2009b;Takahashi et al, 2009). In addition, CYP3A is known to be induced in the small intestine as well as in the liver, and clinical studies have shown that repeated oral administration of representative CYP3A inducers, such as RIF and St. John's wort, resulted in the up-regulation of CYP3A expression in the small intestine (Tannergren et al, 2004;Glaeser et al, 2005) and increased intestinal first-pass metabolism of verapamil, another CYP3A substrate (Fromm et al, 1996). In this study, we used alprazolam (APZ), a known CYP3A probe in humans as well (Schmider et al, 1999) as a marker substrate for pharmacokinetic studies in monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…42 Biotransformation in gut wall contributes substantially to the overall first-pass metabolism of many CYP3A substrates. 43 It is noteworthy that CYP3A4 protein content is approximately three times higher in enterocyte homogenates than in paired liver homogenates. 44 Budesonide is a dual substrate of CYP3A and P-glycoprotein.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the presence of high concentrations of silibinin in the gut just after oral intake and/or as the result of an enterohepatic recirculation may affect gut wall metabolism. CYP3A4 is a major drug metabolising enzyme in the gut wall and makes an important contribution to first pass metabolism of many orally administered CYP3A4 substrates (Fromm et al 1996;Fuhr 1998). Inhibition of intestinal CYP3A4 is the reason for grapefruit juice interactions, which may cause a more than 100% increase in bioavailability of drugs undergoing pronounced first-pass metabolism by gut wall CYP3A4 (Fuhr 1998).…”
Section: Discussionmentioning
confidence: 99%